Students' investigations of torque. (2nd October 2018) - Concannon, James P.; Brown, Patrick L.
Abstract: Students come to class with little understanding about torque, angular velocity, and angular acceleration despite the fact that these physical science concepts are frequently observed. For example, torque occurs when car and bicycle tires rotate, the movement of fishing pole when hooking a fish, and when a person uses a hammer to drive in a nail. Interestingly, students also have a plethora of misunderstandings about scientific inquiry. For example, many students believe that all scientific investigations contain an experiment, and that they are all consist of very specific steps comprising the scientific method. In this week long lesson, 9–12 grade students engage in scientific and engineering practices to examine factors that affect the amount of angular acceleration of a catapult arm. Students also reflect on their own understandings of scientific inquiry within the context of the lesson and address misconceptions they might have. Throughout the activities of this lesson, students to engage in discourse, critical thinking, problem solving, reflection, and modification of ideas to design a catapult that will effectively launch a projectile.